CANVA APPLICATION TRAINING AS A MARKETING DIGITALIZATION MEDIUM FOR SMEs IN DINOYO VILLAGE - Restu Millaningtyas (Universitas Lancang Kuning, 2023)
SMEs owners who lack confidence and experience in creating promotional content, designing logos or brand names, and promoting their products through digital media, including social media and e-commerce platforms, can benefit from training in using the Canva application for digital marketing. The goal of this training is to enhance creativity, innovation, and knowledge of marketing content components. The research method employed in this study is Participatory Action Research (PAR).The training activities proceed smoothly, with participants gaining an understanding of offline and online marketing as well as the components of marketing content. Participants are able to use the Canva application effectively, creating logos and product posters. Moreover, they can leverage the results of logo and poster creation to promote their small businesses on WhatsApp statuses and other social media platforms utilized by the SMEs owners